Optimized Dual-Stokes Raman Laser for 1.1 µm Emission and Temperature Sensing - Jesus Alberto Coba-Ramos; Lelio de la Cruz May; Angeles Yolanda Pages-Pacheco; Efrain Mejia-Beltran; Daniel Jauregui-Vazquez; Manuel May-Alarcon; Rafael Sanchez-Lara; Jose Alfredo Alvarez Chavez (Photonics)
This work experimentally validates an improved Raman fiber laser, developed through cascade core variation splicing of optical fibers and the integration of fiber Bragg gratings. A continuous-wave Yb-doped fiber laser was used as the pump source, delivering up to 10 W at 1064 nm. The first Stokes emission generates laser output centered at 1119 nm, while the second Stokes emission produces a lasing mode at 1179 nm. Fiber Bragg gratings control these emissions. Furthermore, both Stokes laser emissions can be tuned by applying temperature changes, achieving a 15.07 pm/°C sensitivity. The proposed laser presents a compact and practical solution for remote temperature sensing applications using fiber lasers.